If it's not what You are looking for type in the equation solver your own equation and let us solve it.
a15-262=a5-12
We move all terms to the left:
a15-262-(a5-12)=0
We add all the numbers together, and all the variables
-(+a^5-12)+a15-262=0
We add all the numbers together, and all the variables
a^15-(+a^5-12)-262=0
We get rid of parentheses
a^15-a^5+12-262=0
We do not support eapression: a^15
| 3.5(-x+14)=43.5 | | 10=2m-70 | | 3x+12+6x+6=180 | | -83=k-17 | | 5d-6=94 | | -6=-2(3x+5) | | -3(x-5/83=3/16 | | 11x−13x−5x−–18x=11 | | 5f+15=-15 | | –9u+8=–10u | | y-17=-83 | | 26=3x-46 | | –9h+9=–10h | | -n^+32=4n | | 5.9=-z | | -4b-1=-25 | | 100+66x=71x | | u+8=-18 | | 5k-2=-27 | | 6x+6=158-10x | | 7(-6y+8-9=) | | 19+2x=5+4x | | 8+4g=-8 | | 11t+8=52 | | 2x+2x-7+2=4+2(x-5)+2x | | 50+7x=42+15x | | -9x^2+115x-300=0 | | 4-2y=2y | | 10x+18−=2 | | 2x+4 =-1+3x | | (8x^2)-8=24 | | y/12=-5 |